Biomarkers That Currently Affect Clinical Practice in Lung Cancer: EGFR, ALK, MET, ROS-1, and KRAS - Korpanty, Grzegorz J.; Graham, Donna M.; Vincent, Mark D.; Leighl, Natasha B. (Frontiers in Oncology, 2014)
Lung cancer remains the most lethal malignancy in the world. Despite improvements in surgical treatment, systemic therapy and radiotherapy, the 5-year survival rate for all patients diagnosed with lung cancer remains between 15-20%. Newer therapeutic strategies rely on specific molecular alterations, or biomarkers, that provide opportunities for a personalized approach to specific patient populations. Classification of lung cancer is becoming increasingly focused on these biomarkers, which renders the term “non-small cell lung” cancer less clinically useful. Non-small cell lung cancer is now recognized as a complex malignancy and its molecular and genomic diversity allows for patient-centered treatment options. Here we review advances in targeted treatment of lung adenocarcinoma with respect to five clinically relevant biomarkers - EGFR, ALK, MET, ROS-1 and KRAS.